A strain-independent method to induce progressive and lethal pneumococcal pneumonia in neutropenic mice (2015)
ABSTRACT: Background: Experimental models of pneumonia with penicillin non-susceptible Streptococcus pneumoniae (PNSSP) are hard to reproduce because the majority of strains with clinical relevance (like serotypes 6B, 9 V and 19 F) have low murine virulence. By optimization of culture and inoculum conditions of PNSSP (using porcine mucin), our aim was to develop a suitable, reliable and reproducible pneumonia mouse model for anti-infective pharmacology research. Results: Seven PNSSP strains, including serotypes 6B, 9 V, 14 and 19 F were included. Strain INS-E611 displayed the highest murine virulence and was chosen to validate the lung model. Nose-instilled pneumococci grew between 2.1 and 2.5 log10 CFU/g of lung in 24 hours when an optimized culture of bacterial cells was used, but animals were all alive and recovered of infection after 36 h. In contrast, inoculum supplementation with mucin led to 100% mortality related to a successful lung infection confirmed by histopathology. These findings were reproduced with all seven PNSSP strains in neutropenic mice. Immunocompetent animals cleared all strains spontaneously. Conclusions: This pneumonia model produces a progressive and uniformly fatal lung infection with diverse serotypes of PNSSP independently of their intrinsic murine virulence.